Edublogs: An approach to the foreign language curriculum that focuses on core competencies in a global context - García Gómez, Antonio (Pulso. Revista de educación, 2008)
At the beginning of the twenty-first century, Spanish society is convinced both of the need to improve the quality of education, but also to ensure that the benefits reach all young people, without exception. Among some other aims, to encourage lifelong learning means providing young people with an all-round education which covers the knowledge and basic competences necessary in todays society, which allows them to develop values which encourage the practice of active citizenship, community life and social cohesion, which stimulates in them the desire to continue learning and the capacity to learn autonomously. In this context, the present study weighs the pros and cons of using weblogs in education. In doing so, it is argued that these particular weblogs are not only a useful tool in the teaching-learning process of a foreign language, but they are also key to characterising and helping developing students basic competences.
Keywords: Edublogs; Basic Competence; Information and Communication Technology; Cooperative Learning; Learning Strategies and Communicative Approach